A representação da informação no domínio da matemática: análise em linguagens documentárias - MARTINS, Kátia Luciane Macêdo (Universidade Federal do Pará, 2019)
Analyze the natural language of theses and dissertations of the Program of Education in Science and Mathematics (PPGECM),from Federal University of Pará (UFPA), with the general objective of contribute to the reflection of the use of terminologies and documentary languages for information representation in the domain of mathematical sciences and as specific: to investigate in the literature of the information science on documentary languages and terminology for the representation of the information of the Mathematical Sciences domain; to analyze the occurrence of mathematical sciences subjects represented in the natural language of dissertations and theses of the PPGECM / UFPA, comparing with the SIBI-UFPA catalog and with the Library of Congress Subject Headings, an instrument adopted to represent the information in that system; identify the occurrence of the terms in TESAMAT, a specialized instrument in mathematics, ascertaining the adequacy and compatibility with the documentary language adopted by SIBI-UFPA. For this, a bibliographic and documentary research was conducted, being an exploratory study with qualitative approach. It was divided into four stages: a) bibliography analysis; b) identification of theses and dissertations of the PPGECM, in the period 2013-2017; c) elaboration of an electronic form for data collection;d) analysis of the natural language found and its relationship with the SIBI / UFPA catalog and the documentary languages: Library of Congress Subject Headings (LCSH) and the Mathematical Sciences Thesaurus (TESAMAT). As a result, in the terminological analysis of the theses and dissertations, it was found that the terms assigned in the keywords in the natural language (306) were in greater quantity when compared to the indexed terms, taken from documentary languages (210), which were inserted in SIBI-UFPA. This suggests a possible guideline in the indexing process regarding the degree of specificity, with a low comprehensiveness in the identification of subjects in documentary languages. However, in the search was not found any documents with the indexing policy defined in SIBI-UFPA. On the other hand, it was noticed that the choices of the terms in natural language were, for the most part, identified in the LCSH, which shows that the authors of the theses and dissertations analyzed represent in a significant way their themes, evidencing the knowledge of concepts about the terminology indicated in your area. It was still possible to identify that the heading "Mathematics - Study and teaching" was the one that had greater representativeness in the documents analyzed, what suggests a more general terminological catch on the subject of this research, being found in the LCSH and the TESAMAT. Finally, we conclude by the importance of studies on documentary languages to guarantee the representation of the scope of the document, counting on the praxis of indexation and, with specific instruments for the determination of the subject, particularizing the scientific researches, in order to avoid more than one interpretation in documentary practices.